Raziskava o sprejemljivosti komasacije za urbano prenovo v Hongkongu - Yau, Yung (Urbani izziv, 2009)
In view of the ever-increasing problem of urban decay in Hong Kong, the authorities have paid huge efforts in renewing the city. Yet, redevelopments are often delayed owing to the thorny and lengthy exercises of land assembly. While compulsory purchase or eminent domain helps to speed up the land assembly process, this approach has been criticized for creating social tensions between the redevelopment agents and those affected homeowners. Otherthan protection of private property rights, some of the affected homeowners pursue a course of action in order to be entitled to redevelopment gains. Besides all of the above, forced displacement by redevelopment may seriously disrupt the social network system. In light of these predicaments, the technique of land readjustment (LR) has been proposed. In principle, the LR technique can foster a partnering relationship among various stakeholders of a redevelopment project. Although LR has been practised overseas for various purposes, its applicability to redeveloping buildings in Hong Kong's urban is moot. This article aims to explore the acceptability of LR in Hong Kong through a structured questionnaire survey of 356 residents in Kowloon City. Based on this survey's findings, some policy and practical implications are drawn and discussed. On the issue of sustainable urban regeneration, these implications offer valuable insights to public administrators and urban managers.
Keywords: Hongkong; komasacija; mesta; odkup; prenova; zemljišča